Time to invest in cholera - Rebecca C. Stout; Nicholas Feasey; Marion Péchayre; Nicholas Thomson; Benson Z. Chilima (EClinicalMedicine)
Summary: The recent surge in cholera cases globally calls for urgent evaluation of current approaches to prevention and control of the disease. Malawi was one of the worst affected countries in 2022–2023 with the highest number of deaths due to cholera in the world. In this personal view, we look at Malawi as a case example to illustrate how current approaches lack sufficient investment. We review the history of cholera in Malawi and compare previous outbreaks to the 2022/23 outbreak. We discuss contributing factors to the outbreak including a lack of investment in water, sanitation and hygiene (both historically and currently), human resource constraints, and the market structures which make accessing oral cholera vaccine challenging both in the midst of an ongoing outbreak and as a preventative approach. We call for international action to address the economic and structural challenges underlying cholera persistence and propose solutions to prevent future epidemics and to eliminate cholera as a public health threat.